Isothermal decomposition kinetics in the Cu-9%Al-4%Ag alloy - Adorno, A. T.; Silva, RAG (Elsevier B.V., 2004)
The influence of 4 wt.%Ag addition on the isothermal decomposition kinetics of the beta' phase in the Cu-9wt.%Al alloy was studied by microhardness measurements, optical and scanning electron microscopy (SEM), energy dispersive X-ray (EDX) analysis, and X-ray diffractometry. The results showed that the presence of Ag decreases the beta' --> (alpha + gamma(1)) decomposition reaction rate in the Cu-9%Al-4%Ag alloy, an effect that may be associated to the gamma(1) phase which catalyses the Ag precipitation, making it faster than the decomposition reaction, and thus, stabilizing the martensitic phase. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: metals; precipitation; x-ray diffraction